Relevansi Dimensi Sosial-Spiritual dalam Psikologi Islam: Analisis Pemikiran Imam Al-Ghazali Dan Hasan Langgulung - Abrori Abrori; Moh. Wardi; Aldo Redho Syam (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – The integration of social and spiritual dimensions constitutes a fundamental foundation in Islamic psychology. However, in contemporary discourse, these two dimensions are often treated as separate constructs. This study aims to analyze the relevance of the social and spiritual dimensions within the framework of Islamic psychology through a comparative examination of the thoughts of Imam Al-Ghazali and Hasan Langgulung. Grounded in the assumption that psychological well-being in Islam is inherently relational and transcendental, this research seeks to formulate a conceptual synthesis that bridges classical and modern perspectives.Methods – This study employs a narrative literature review approach by systematically examining primary and secondary sources related to the ideas of both scholars, along with recent literature on social support, spirituality, and character education.Findings – The findings indicate a clear epistemological continuity between Al-Ghazali’s concept of purification of the soul as the ethical foundation of social life and Langgulung’s integrative educational framework, which emphasizes the harmonization of intellectual, social, and spiritual aspects in the development of mental health. Research Implications – The novelty of this study lies in proposing an integrative socio-spiritual framework that understands psychological well-being not merely as emotional and cognitive stability, but as a balanced social relationship grounded in spiritual values. The implications highlight the importance of adopting a holistic approach in psychological practice, particularly within Muslim communities, by integrating social relational aspects, the search for life’s meaning, and the strengthening of spirituality in both assessment and intervention processes.